Costituzione e generi: argomenti interpretativi e teorie sulla differenza sessuale (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The paper hangs out the main arguments used to interpret constitutional principles regarding gender issues. These arguments are considered to the light of the most widespread theories about sexual difference. Moreover, the analysis critically deals with constitutional judgments regarding political representation and suggests reading the political representation theory to the light of the dilemmatic approach of sexual difference.
Keywords: Gender; constitutional principles; interpretation; political representation theory; dilemmatic approach of sexual difference